The Dynamic Problems of Polygamy Cases in Indonesia:: The Showcase of Juridical Authority, Implementation of Contra Legem and Fiqh Argumentations - Naily, Nabiela; Riza, A. Kemal; Biroroh, Ta’mirotul (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Abstract: One issue that remains a stumble block for modernization of Islamic family law is polygamy. In Indonesia, polygamy is restricted, but not completely forbidden. Husbands who have desires for polygamy should fulfill requirements before the court of justice. However, there is a tendency among judges of Islamic courts nowadays to grant permission for them to practice polygamy although not all of those husbands meet the requirements as outlined by the Marriage Law. The judges argue that according to Article 5 the Law No. 48 of 2009 concerning Judicial Authority they have the right and are obliged to deliver justice at all costs. Therefore, they grant permission for polygamy not only on the basis of the corresponding the Law No. 1 of 1974 on Marriage, but also on the authority of rechtsvinding, Islamic jurisprudence or fiqh as living law concept, and contra legem theory, a progressive implementation of legal value. Keywords: polygamy, juridical authority, contra legem